ASPEK-ASPEK PENDIDIKAN ISLAM DALAM PERSFEKTIF AL-QUR’AN - Hubbil Khair (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
The aspect of Islamic education is essentially a process that knows no age limits. The education is based on the Quran and the Hadith of the Prophet, which aims to form a collective piety. With the existence of Islamic education it is hoped that a Muslim can become good, both for himself and good for others. The aspect of Islamic education based on the values of the Sirah Nabawiyah teaching is an integration of educational components that are closely related to one another. The relationship between these aspects is not a relationship without direction, but has a noble goal, which is to form good human beings and have qualities in the spiritual-religious and intellectual field.